2019
DOI: 10.1002/ece3.4899
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of the growth of Anolis nebulosus (Squamata: Dactyloidae) in a seasonal tropical environment in the Chamela region, Jalisco, Mexico

Abstract: Juvenile growth rates are thought to be restricted by available food resources. In animals that grow throughout the year, such as tropical lizards, growth is therefore predicted to be faster during the rainy season. We test this prediction using a population of Anolis nebulosus by describing the growth trajectories of both sexes using nonlinear regression models, and we then correlate the growth rates of individuals with food available in the environment, precipitation, and temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(130 reference statements)
0
6
0
2
Order By: Relevance
“…First, numerous capturerecapture field studies (e.g. [25,[36][37][38][39]), as well as laboratory experiments (e.g. [40,41]), involving distantly related species of reptiles suggest that growth is minimal or non-existent in older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…First, numerous capturerecapture field studies (e.g. [25,[36][37][38][39]), as well as laboratory experiments (e.g. [40,41]), involving distantly related species of reptiles suggest that growth is minimal or non-existent in older individuals.…”
Section: Introductionmentioning
confidence: 99%
“…However, it would be difficult to test this hypothesis, since few studies have demonstrated this relationship reliably (Berns 2013). For example, Márquez et al (2005), Siliceo-Cantero et al 2016and Hernández-Salinas et al (2019), observed that differences in growth rates and head size between the sexes in A. aquaticus and A. nebulosos allow them to feed on different types of prey during their development. Butler et al (2000) noted that the sexual dimorphism recorded in Anolis species of the Greater Antilles was correlated with the type of microhabitat and perch height that males and females use.…”
Section: Resultsmentioning
confidence: 99%
“…SD in the genus Anolis has been explained with reference to gular dewlap and other morphologic traits associated with body shape (ecomorphs) in West Island Anolis lizards (Butler et al 2007;Losos 2009;Johnson and Wade 2010), while SD in mainland Anolis species has mostly been related to SVL, perch use, and diet (Perry 1996;Ramírez-Bautista and Vitt 1997;Ramírez-Bautista and Benabib 2001). Despite this, there is little information about SD in most of the mainland Anolis species; therefore, it is necessary to determine whether SD occurs in other morphological structures beyond previously reported (Márquez et al 2005;Siliceo-Cantero et al 2016;Hernández-Salinas et al 2019). Therefore, the goal of this study is to analyze the SD of a tiny mainland anole species Anolis unilobatus Köhler and Vesely 2010; east pacific and central depression Chiapas clade see Gray et al 2019 (We will refer as Anolis unilobatus to the populations of the east pacific lineage, but we are aware of these populations belong to an evolutionarily independent lineage to the populations of the west pacific and of central America Gray et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger males are better able to defend territories during reproduction because they have higher success rates in malemale combat. In addition, growth rate is faster in males than in females, as explained by the fact that they must prepare (during reproductive period) the site of courtship, mating and fertilization of eggs (Hernández-Salinas, Ramírez-Bautista, Cruz-Elizalde, Meiri, & Berriozabal-Islas, 2019;Ramírez-Bautista & Vitt, 1997). Female-biased SSD provides larger body sizes, which in females can increase fecundity by increasing space for developing embryos, allowing either for larger litter sizes or for larger body sizes at birth (Olsson et al, 2002;Pincheira-Donoso & Hunt, 2015;Scharf & Meiri, 2013).…”
mentioning
confidence: 99%